(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
Speech etiquette is a vital component of the tourism industry, serving as the linguistic bridge between diverse cultures. However, when the cultural codes of a tourist and a service provider (guide, hotelier, or agent) do not align, communication barriers arise, leading to pragmatic failure and negative tourist experiences. This article explores the linguistic and cultural obstacles in tourism-related discourse. It analyzes how polite forms, speech acts, and non-verbal cues differ across cultures and proposes practical solutions for enhancing intercultural communicative competence among tourism professionals.